High-intensity functional training: association of body fat with cardiorespiratory fitness - Brian Johan Bustos-Viviescas; Luis Alfredo Duran-Luna; Rony David Merchan Osorio; Arles Javier Ortega Parra; Andres Alonso Acevedo-Mindiola; Carlos Enrique Garcia Yerena (Revista Cubana de Medicina Militar)
Introduction: The High-Intensity Functional Training (HIFT/CrossFit®) is characterized by high-intensity multimodal exercises. Within the research field little has been addressed on this novel modality, it is for them that the need arises to examine the anthropometric and cardiorespiratory characteristics of HIFT/CrossFit® practitioners. Objective: Determine the association between body fat and cardiorespiratory fitness in HIFT/CrossFit practitioners®. Method: Descriptive study of correlational type with quantitative approach and a sample at the convenience of 8 subjects, 4 men (age 21,75 ± 3,10 years; body mass 83,85 ± 13,98 kg; size 1,79 ± 0,08 m) and 4 women (age 26,00 ± 8,52 years; body mass 62,80 ± 5,99 kg; size 1,65 ± 0,04 m) experienced HIFT/CrossFit® practitioners; all of them volunteer participants who underwent the cardiorespiratory fitness assessment test and anthropometric characteristics assessment; the data from the study were analyzed with the PSPP statistical package, where Spearman's correlation coefficient and normality test (Shapiro-Wilk) were applied. Results: A negative and significant relationship (p < 0,05) is shown in men (r = -0,94) and women (r = -0,95), although the whole group had greater significance of body fat with cardiorespiratory fitness (r = -0,87; p < 0,01). Conclusion: Higher percentage of body fat results in lower cardiorespiratory fitness in subjects trained in high-intensity functional training.